Doing Qualitative Research in a Controlled Site: Challenges, Lessons, and Strategies - Baffour, Frank Darkwa (Crime & delinquency, 2024)
This paper reflects on the process of undertaking qualitative research with incarcerated individuals and prison staff in selected Ghana prisons. The challenges encountered during the planning, approval, and fieldwork stages, as well as measures adopted to address these challenges, have been discussed. The paper aims to serve as a guide to novel prison researchers in the sub-Saharan African context, given that the majority of studies on challenges and approaches to conducting prison research have come from jurisdictions outside the region. To this end, given the unique nature of the prison governance system in Ghana and other sub-Saharan African countries, this paper contributes to filling a knowledge gap in qualitative prison research.